PERSENTASE BONELESS, TULANG, DAN RASIO DAGING – TULANG AYAM BROILER PADA BERBAGAI BOBOT POTONG - Patriani, Peni; Hafid, Harapin (Journal Galung Tropika, 2019)
The research aims to determine the effect of the range of cut weight on the percentage of boneless chicken meat, using a Completely Randomized Design. Research material using 14 broilers were purchased from farmers by selecting chickens randomly according to the desired body weight range. The treatment were in the form of a classification of the weight range of cut, 851-1,850 g, 1,051-1,250 g, 1,251-1,450 g and 1,451-1,700 g. The observed variables were cutting weight, carcass weight percentage, boneless percentage, meat percentage, and bone ratio. The results showed that broiler cutting weight had a very significant effect (P<0.01) on the percentage of boneless. The greater of the weight of the cut means the greater percentage of boneless produced. Broiler cut weight did not have a significant effect (P>0.05) on the percentage of bone and bone meat ratio. It was concluded that the greater weight of the broiler cut showed the increase in the percentage of boneless chicken greater. This indicates the increased content of boneless meat produced.